2011
DOI: 10.1104/pp.111.172221
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Hemicellulose Contributes Significantly to Aluminum Adsorption and Root Growth in Arabidopsis

Abstract: The cell wall (CW) has been recognized as the major target of aluminum (Al) toxicity. However, the components responsible for Al accumulation and the mechanisms of Al-induced CW function disruption are still elusive. The contribution of different CW components (pectin, hemicellulose 1 [HC1], and HC2) to adsorb Al and the effect of Al on xyloglucan endotransglucosylase/ hydrolyase activity were investigated in Arabidopsis (Arabidopsis thaliana) in this study. A fractionation procedure was optimized to effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
231
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 312 publications
(241 citation statements)
references
References 36 publications
10
231
0
Order By: Relevance
“…Using artificial pectin membranes, Blamey et al (1993) demonstrated that the binding of Al to pectin strongly reduced water permeability of the membranes. Recently, hemicellulose rather than pectins have been implicated in Al binding in CWs (Yang et al 2011a). Further studies in Arabidopsis thaliana (L.) Heynh provided evidence that Al interacts specifically with xyloglucans (Zhu et al 2012).…”
Section: Aluminium Toxicity and Root Water-relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using artificial pectin membranes, Blamey et al (1993) demonstrated that the binding of Al to pectin strongly reduced water permeability of the membranes. Recently, hemicellulose rather than pectins have been implicated in Al binding in CWs (Yang et al 2011a). Further studies in Arabidopsis thaliana (L.) Heynh provided evidence that Al interacts specifically with xyloglucans (Zhu et al 2012).…”
Section: Aluminium Toxicity and Root Water-relationsmentioning
confidence: 99%
“…Under Al stress, Al strongly binds to the negative charges provided by the carboxylic groups of galacturonic acids of the pectins (Blamey et al 1990;Chang et al 1999) and to hemicellulose (Yang et al 2011a). There is little doubt that the high affinity of Al to the pectic matrix and hemicellulose will substantially affect the chemical and mechanical properties of the CW, and this Al-apoplast interaction has been proposed as the main cause of Al-induced inhibition of root elongation .…”
Section: Cell-wall Extensionmentioning
confidence: 99%
“…For example, the most significant Al-induced change in cell wall components involves the hemicellulose fraction in wheat (Triticum aestivum; Tabuchi and Matsumoto, 2001), triticale (X Triticosecale Wittmack; Liu et al, 2008), and rice (Oryza sativa; Yang et al, 2008), especially in Al-sensitive cultivars. Moreover, we found that in Arabidopsis thaliana, hemicellulose is not only susceptible to Al stress but is also the principal binding site for Al; the amount of Al accumulated in hemicellulose is much more than that in pectin (Yang et al, 2011), although how hemicellulose can bind Al is unclear. Thus, the role of not only pectin but also hemicellulose in Al toxicity/resistance and its underlying physiological and molecular mechanisms need to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…The extraction of pectin was carried out by washing approximately 2 mg of isolated cell walls three times with 1 mL water at 100°C for 1 h. The supernatants containing pectin were collected in a 5-mL tube after centrifugation at 13,200 rpm for 10 min (Zhong and Läuchli, 1993;Yang et al, 2011).…”
Section: Cell Wall Extraction and Fractionationmentioning
confidence: 99%